2017
DOI: 10.3390/su9081393
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Rural Household Livelihood and Regional Ecological Footprint in Water Source Areas of the South-to-North Water Diversion Project

Abstract: Abstract:There is a knowledge gap and practical demand to understand the co-evolutionary relationship between rural household livelihood and regional ecological footprints for developing sustainable livelihoods in ecological conservation regions. This paper tracks the change trajectories of rural household livelihoods and regional ecological footprints in four water source areas of the South-to-North Water Diversion Project where various ecological and environmental protection projects and measures are being p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Taking the South-North Water Transfer Middle Route Project as an example, Wei and Xia [33] calculated the losses of ecological immigrants and provided a more reasonable compensation amount based on the ecological footprint theory. Wang, et al [34] tracked the change trajectories of rural household livelihoods and regional ecological footprints in four water source areas (Shiyan, Nanyang, Tai'an, and Jining) of the South-to-North Water Diversion Project in 2000-2014. Wang, et al [35] assessed the positive and negative impacts of cascaded diversion small hydropower (SHP) on environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taking the South-North Water Transfer Middle Route Project as an example, Wei and Xia [33] calculated the losses of ecological immigrants and provided a more reasonable compensation amount based on the ecological footprint theory. Wang, et al [34] tracked the change trajectories of rural household livelihoods and regional ecological footprints in four water source areas (Shiyan, Nanyang, Tai'an, and Jining) of the South-to-North Water Diversion Project in 2000-2014. Wang, et al [35] assessed the positive and negative impacts of cascaded diversion small hydropower (SHP) on environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Eco-accounting is used for the generation, analysis and use of financial and related non-financial information in order to effectively solve the problems encountered in the process of sustainable development [1,2]. As a tool to report sustainable impacts, it has been applied in ecological footprint measurements, e.g., water footprint [3][4][5] and carbon footprint [6,7], soil quality assessment [8], ecosystems [9] and energy efficiency [10]. Studies have revealed that eco-accounting is able to calculate environmental impacts from various aspects, however, incorporating lifecycle impact assessment methods into the eco-accounting framework would provide an extended eco-accounting solution from the perspective of products' life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…With this solution, the accounting will be able to cover major environmental impact categories through the product's business supply chain and to share the eco-accounting results among stakeholders, which would be one step further to support sustainable development in the circular economy context. Many scholars have applied the conventional eco-accounting merits for major stakeholders of supply chains in various scenarios such as eco-innovation for businesses [11][12][13], and decision making for policy implications [4,6]. However, few studies have accommodated the eco-accounting results for consumers and other stakeholders of the product supply chain.…”
Section: Introductionmentioning
confidence: 99%